(3GdaQjOI GdSfjI aj GdMce GdYQHjIs - (3eMeO Cejf Hf NjQ Gddg Hf eMehO Hf ehSi GdNWjH, GdYeQj,J (B1203 (3g` s
(3ChdgG (B:s
(3hHYO TeS GdOjf eMeO Hf Ydj GdTGej gPg ZQQ habj haQGFO hOQQ cGfJ YfOj aj QSGFd s
(3BNQgG (B:s
(3Edi ce JeGO aj YQhQ hZadI hce gcPG fhe Edi ZjQ jbXI GdJbWJ gPg GdaQGFO hGdOQQ hGdZaQGf ef cHJ YOI s
(3GdeNWhWI efShHI NWC dTeS GdOjf eMeO Hf Ydj GdTGej hGdUhGH eG CKHJfGgs
(3HChdgG hba GdeNWhWI eDQN YGe (B1192 (3g```s
(3ChbagG GdhRjQ SdjeGf HGTG eMeO Cejf Hf GdMGL MSjf GdLdjdjs
(3hHgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdCOHs